Recognizing and Describing the Factors Affecting the Design of the Innovation Ecosystem Model in the Field of Health with an Emphasis on the Role of E-Government - Zahra Mirjalili; Abbas Babaeinejad; Saeed Sayadi; Hamid Reza Mollaei (Journal of Community Health Research)
Background: Development of innovation issues in countries has led to the formation of new concepts in this field. Some of these concepts include innovation systems ranging from national, sectoral, etc., innovation networks, commercialization, and innovation ecosystems. Therefore, the purpose of this study is to design recognition and description of the factors affecting the design of the ecosystem model of innovation in the field of health with an emphasis on the role of e-government. Methods: The type of qualitative study is a type of theory. A semi-structured interview was used to gather information. And the analysis of Strauss and Corbyn's method and the paradoxical model were used. The samples were selected through targeted sampling. And finally, 7 senior and middle managers of government and non-governmental hospitals in Yazd province entered the study. Results: The model designed in this study includes the effective dimensions and components, obstacles and strategies, causal conditions, contextual, intermediary and constituent elements that are the pivotal phenomenon, Shows the consequences and strategies. identifiers and Ecosystem Factors Innovation 37 Concepts, 4 Main categories Enabling policies and regulations, Access to data and infrastructure، funding and validation opportunities and ease of acceptance and dissemination of innovations (from interviews and research literature) were formulated in the form of a conceptual model Conclusion: The process of study was explained in the form of the story line of the electronic government data theory. Finally, the innovation ecosystem model in the field of biotechnology was designed and analyzed. Finally, this model can be used to design an innovation ecosystem in the field of health.